Development of software for analyzing step length courses in sprint dash with the use of the laser velocity measuring device and digital video camera - Kintaka, H.; Urita, Y.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
We have developed software (sprint-performance analyzer: SPA) for estimating step length courses in sprint dash with the use of the laser velocity measuring device and digital video camera. It gives a quick feedback to coaches and athletes and helps to evaluate performance of athletes. In this research, we compared time of analyzing by the SPA with that not utilizing the software. In addition, step length courses estimated in this measuring method were reexamined. A statistical analysis was done between estimated step length (ESL) by SPA and actual step length (ASL) by using Two-dimensional motion analysis method. Time of analyzing by SPA was 10 minutes/trial, which was shorter than 50 minutes/trial of that not utilizing the software. There were very small differences (?d) between the filtered ESL and the filtered ASL at respective trials (?d=0.00-0.04m).